Understanding the Nexus between Green Entrepreneurship and Green Economy: A Review - Purnomo, Agung; Asitah, Nur; Rosyidah, Elsa (Cv. Syntax Corporation Indonesia, 2023)
The role of green entrepreneurship is sufficient to realize a green economy. This study aims to understand the existing literature and research on green entrepreneurship in the green economy. The literature was reviewed systematically following the PRISMA guidelines for performing and reporting systematic literature reviews. Some reviewed articles were included based on a systematic search of the Scopus database. The research agenda was provided using quantitative, multilevel, and management perspective analysis. Continental Europe has made the most contributions to this field. The developments in green entrepreneurship research in the green economy can be attributed to several factors, such as environmental concern, SDGs, resource efficiency, climate change mitigation, innovation, social inclusion and measurement. Further research can be carried out using the team level by connecting the management perspective of finance, operation and human resource.